THE PESTICIDES RISKS FOR RURAL WORKER IN THE PERSPECTIVE OF THE 18TH REGIONAL LABOR COURT (CIPEEX, 2022)
THIS PAPER AIMED TO ANALYZE HOW THE JUDGES AND JUDGES OF THE REGIONAL LABOR COURT OF THE 18TH REGION, BASED IN GOINIA, GOIS, HAVE JUDGED THE COMPENSATION CLAIMS FILED BY RURAL AGRICULTURAL WORKERS VICTIMS OF PESTICIDE POISONING IN THE WORK ENVIRONMENT. CONSIDERING THAT THE LABOR COURT EMERGED AS AN INSTITUTION UMBILICALLY LINKED TO THE REALIZATION OF SOCIAL RIGHTS, DOES THE COURT IN QUESTION APPRECIATE SUCH CASES BASED ON THE MISSION OF THE JUDICIARY IN THE CONTEXT OF A DEMOCRATIC STATE OF LAW? THE THEORETICAL FRAMEWORK WAS SUPPORTED BY THE CONCEPTS OF DEMOCRACY, DEMOCRATIC STATE OF LAW AND DEMOCRATIC JUDICIARY PRESENTED BY MAURCIO GODINHO DELGADO. THE WORK WAS DIVIDED INTO FOUR CHAPTERS. IN THE FIRST CHAPTER, A THEORETICAL APPROACH ON FUNDAMENTAL RIGHTS WAS CARRIED OUT, AND AS THE FEDERAL CONSTITUTION OF 1988 GUARANTEES RURAL WORKERS VICTIMS OF PESTICIDE POISONING THE RIGHT TO OBTAIN DUE REDRESS FROM THEIR EMPLOYERS, BASED ON OBJECTIVE ACCOUNTABILITY, THAT IS, REGARDLESS THE EXISTENCE OF INTENT OR GUILT (RECKLESSNESS, MALPRACTICE OR NEGLIGENCE). IN THE SECOND CHAPTER, DECISIONS RENDERED IN THE FIRST AND SECOND DEGREES OF JURISDICTION WERE ANALYZED IN THE REGIONAL LABOR COURT OF THE 18TH REGION, AND VERIFIED THAT, DESPITE THE EXISTENCE OF THE RIGHT OF RURAL WORKERS TO COMPENSATION BASED ON STRICT LIABILITY, IN THE SAID COURT THE DECISIONS OF THE MAGISTRATES FIX, BY DEFAULT, SUBJECTIVE RESPONSIBILITY, THAT IS, THEY CONDITION REPARATION TO THE PRESENCE OF INTENT OR GUILT ON THE PART OF RURAL EMPLOYERS. IN CHAPTER THREE, THE FORMATION AND CONCEPT OF THE DEMOCRATIC STATE OF LAW, AND THE ROLE OF THE JUDICIARY AND JUDGES IN A DEMOCRACY WERE ADDRESSED, IN ORDER TO IDENTIFY, IN THE FOURTH CHAPTER, THE REASONS AND IMPLICATIONS OF THE DISSONANCE BETWEEN WHAT IS OBSERVED IN THE NORMATIVE FRAMEWORK AND WHAT IS ACTUALLY DECIDED IN THE REGIONAL LABOR COURT OF THE 18TH REGION, IN RELATION TO THE CLAIMS FOR INDEMNITY DEDUCTED BY RURAL WORKERS VICTIMS OF ACCIDENTS WITH PESTICIDES.
Keywords: pesticides; rural worker; labor court